EFFECTIVENESS OF MEDIATION IN THE DISPUTE RESOLUTION OF ISLAMIC ECONOMICS IN INDONESIAN RELIGIOUS COURTS - Setyowati, Ro’fah; Musjtari, Dewi Nurul; Susilowati, Indah (UI Scholars Hub, 2021)
Mediation is a mandatory procedure in the resolution of civil cases in the courts since 2003. In the implementation of the Islamic banking dispute settlement after the Constitutional Court decision No. 93 / PUU-X / 2012 in the Religious Courts, mediation mechanisms demonstrates increasing success, to an average of 10%. Based on this phenomenon, it is important to do research to know the depth of the effectiveness of mediation in the settlement of disputes in the Indonesian Religious Courts. This study aims to discover the reasons for the selection of mediation as a dispute resolution mechanism syariah economic cases, and to analyze the factors that may affect the success of mediation in the Religious Courts in Indonesia. Some theories used to analyze in this research is the theory of operation of the law by Robert B. Seidman and sibenertika theory of Talcot Parson, as well as the effectiveness of law enforcement concepts according Soerjono Soekanto. This study is a socio-legal or juridical empirical research, using qualitative analysis and approach to philosophical, historical, and juridical. Based on this research, it was found that the concept of mediation is appropriate to be applied to the Religious Courts in Indonesia. It thus known from the cultural aspects of law enforcement with the parties to the dispute in the Religious Courts. Moreover, the attitudes of the Muslim community who like peace provide a positive stigma and support to the judiciary, as well as encourage the compliance of parties to implement the decision. Professionalism among judges as mediators maintained sidiq nature, mandate, sermons and fathonah is one of the factors that influence the success of mediation Religious Courts in Indonesia.